2017
DOI: 10.1007/s10792-016-0427-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of adding ripasudil to existing treatment regimens for reducing intraocular pressure

Abstract: Adding ripasudil to existing glaucoma treatment regimens is effective and safe in reducing IOP, regardless of the number of medications in use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…A prospective case series study by Inazaki, et al recruited 35 patients who had POAG and poor IOP control under maximally tolerated medications and found that the addition of ripasudil for 3 months resulted in a 2.8 mmHg IOP reduction on average [13], which is similar to our result of the magnitude of IOP reduction in patients with POAG being 2 mmHg. Similarly, Inoue, et al found the additive IOP-lowering effect of ripasudil in a total of 119 eyes of 119 patients with POAG or ocular hypertension, who had already used two or more anti-glaucoma medications [14]. In their study, the average IOP before the initiation of ripasudil application was 19.8 mmHg, while the IOP at 1 month and 3 months after the initiation was 17.5 and 16.8 mmHg, respectively [14].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…A prospective case series study by Inazaki, et al recruited 35 patients who had POAG and poor IOP control under maximally tolerated medications and found that the addition of ripasudil for 3 months resulted in a 2.8 mmHg IOP reduction on average [13], which is similar to our result of the magnitude of IOP reduction in patients with POAG being 2 mmHg. Similarly, Inoue, et al found the additive IOP-lowering effect of ripasudil in a total of 119 eyes of 119 patients with POAG or ocular hypertension, who had already used two or more anti-glaucoma medications [14]. In their study, the average IOP before the initiation of ripasudil application was 19.8 mmHg, while the IOP at 1 month and 3 months after the initiation was 17.5 and 16.8 mmHg, respectively [14].…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, Inoue, et al found the additive IOP-lowering effect of ripasudil in a total of 119 eyes of 119 patients with POAG or ocular hypertension, who had already used two or more anti-glaucoma medications [14]. In their study, the average IOP before the initiation of ripasudil application was 19.8 mmHg, while the IOP at 1 month and 3 months after the initiation was 17.5 and 16.8 mmHg, respectively [14]. The present results of patients with POAG were also in agreement with their study.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…[6][7][8][9][10][11] Ripasudil has a different IOP-lowering mechanism from the existing antiglaucoma instillations; therefore, it is expected to be used in combination with conventional antiglaucoma ophthalmic solutions. Although many studies have already reported the short-term IOP reduction and adverse effects associated with ripasudil treatment, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] the long-term efficacy of ripasudil over more than 1 year has been addressed by only a few studies. 28,29 In addition, relatively few studies have evaluated the clinical factors affecting IOP reduction in cases wherein ripasudil was an addition to or a switch from the existing antiglaucoma instillations.…”
Section: Introductionmentioning
confidence: 99%